Release : a model with data to predict aerosol rainout in accidental releases - Johnson, David W., 1942- (CCPS concept book., 1999)
This book documents CCPS's Aerosol Research Program to develop a model to predict liquid rainout from release of a pressurized, liquefied gas--and, hence the residual amount of material in a vapor cloud, which may be greater than the amount calculated from an enthalpy chart. RELEASE predicts the rate of fluid discharge, the depressurization, flashing and formation of liquid drops, the entrainment of drops into the vapor cloud, the subsequent spreading of the jet, and rate of liquid rainout to a pool on the ground. Designed in a modular fashion to permit adjustment and corrections as new data b.